Особенности дефектообразования при импульсном ударном сжатии - Мазанко, В.Ф.; Михаленков, В.С.; Цапко, Е.А.; Богданов, Е.И.; Бевз, В.П.; Ворона, С.П. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of studies of the peculiarities of the mass-transfer and defect-forming in Cu under pulse shock compression and rolling by using a radioactive isotope (63Ni) and positron spectroscopy are presented. It is established that the pulse shock compression leads to the acceleration of the mass-transfer. Under rolling, this effect was not observed. The mass-transfer coefficients and their dependence on the shock compression parameters are determined. It is shown that no vacancies are formed under the shock treatment. Therefore, they are not responsible for the mass-transfer acceleration.